How young children learn to think : a discussion with Constance Kamii - Kamii, Constance (Washington, D.C. : National Association for the Education of Young Children (NAEYC), 1985)
Clear, concise explanation of Piaget's theory of how children acquire knowledge.
DVD.
Keywords: Piaget, Jean; Child development; Cognition in children; Education, Preschool -- 1965-